Periphrastic voice with see in Portuguese - Lehmann, Christian (2010)
Several European languages have periphrastic constructions involving “see” as avoiceauxiliary, inparticular areflexiveconstruction suchasthefollowing fromPortuguese:aempresaviu-seobrigadaadespedir30trabalhadores“the company found itself forced to lay off 30 workers”. This construction is the passive of “see”. Passives of “see” can be derived systematically from nonreflexive constructions involving dependent past participial and infinitival clauses whose subjects are not co-referential with the subject of “see”. In this perspective, the passive of “see” emerges as an instance of a more general pattern, specialized by use of the reflexive verb form and the past participial clause. The object of this study is the Portuguese ver-se passive. The paradigmatic relations of this construction to active constructions and to other periphrastic voices as well as its semantic constraints are analyzed, and its origins in the history of the language are traced. We claim that the construction is well underway to grammaticalization.